Association between exposure to ambient air pollutants and the outcomes of in vitro fertilization treatment: A multicenter retrospective study. (August 2021) - Wu, Shanshan; Zhang, Yunshan; Wu, Xueqing; Hao, Guimin; Ren, Haiqin; Qiu, Jiahui; Zhang, Yinfeng; Bi, Xingyu; Yang, Aimin; Bai, Lina; Tan, Jichun
Highlights: The first large-scale multicenter retrospective study conducted in Northern China. Both outcomes of fresh and frozen-thawed embryo transfer cycles in IVF were explored. Exposure to O3, CO, and NO2 are negatively associated with fresh transfer outcomes. SO2 exposure is inversely correlated with pregnancy outcomes in FET cycles. Air pollution is associated with higher risk of ectopic pregnancy and lower oocyte yield. Abstract: Background: Exposure to ambient air pollution has been reported to be inversely correlated with human reproductive health. However, the results of previous studies exploring the association between air pollution and in vitro fertilization (IVF) outcomes are conflicting, and further research is needed to clarify this association. Objectives: This study aimed to investigate the associations between exposure to air pollutants and IVF outcomes. Methods: We conducted a multicenter retrospective cohort study involving 20, 835 patients from four cities in Northern China, contributing to 11, 787 fresh embryo transfer cycles, 9050 freeze-all cycles, and 17, 676 frozen-thawed embryo transfer (FET) cycles during 2014–2018. We calculated the daily average concentrations of six criteria air pollutants (PM2.5, PM10, O3, NO2, CO, and SO2 ) during different exposure windows in IVF treatment timeline using data from the air monitoring station nearest to the residential site as approximate individual exposure. Generalized estimation equation models were used to assess the association between air pollution exposure and IVF outcomes. Results: Exposure to O3, NO2, and CO during most exposure windows in fresh embryo transfer cycles were correlated with lower possibilities of biochemical pregnancy, clinical pregnancy, and live birth. An inverse association of exposure to O3 and SO2 with pregnancy outcomes was observed in FET cycles. In addition, we found a significant association of exposure to air pollutants with a higher risk of ectopic pregnancy and lower oocyte yield. Conclusions: Our study provided large-scale human evidence of the association between air pollution and adverse human reproductive outcomes in the population opting for IVF. Thus, exposure to air pollutants in the population opting for IVF should be limited to improve treatment outcomes.